The Development of Space Law: Applying the Principles of Space Law and Interpreting 'Peaceful Purposes' in the Outer Space Treaty 1967 - Fradhana Putra Disantara (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This study analyzes the relevance of the proportionality, non-intervention, and unnecessary suffering principle's in the outer space perspective; and analyzes the 'peaceful purposes' at Outer Space Treaty 1967. This legal research uses primary and secondary legal materials to obtain an appropriate analysis of legal issues. This research states that the principles of international law must be applied in space activities by outer space actors. Furthermore, the ambiguity of the phrase 'peaceful purpose' in the Outer Space Treaty gives rise to different interpretations by each state. For this reason, a convention on outer space is needed to affirm the orientation of 'peace' in space activities.